Challenging the Norm: The Unrecognized Impact of Soluble Guanylyl Cyclase Subunits in Cancer - Pino, María Teresa Luján (2024)
Since the discovery of nitric oxide (NO), a long journey has led us to the present, during which much knowledge has been gained about its pathway members and their roles in physiological and various pathophysiological conditions. Soluble guanylyl cyclase (sGC), the main NO receptor composed of the sGCα1 and sGCβ1 subunits, has been one of the central figures in this narrative. However, the sGCα1 and sGCβ1 subunits remained obscured by the focus on sGC’s enzymatic activity for many years. In this review, we restore the significance of the sGCα1 and sGCβ1 subunits by compiling and analyzing available but previously overlooked information regarding their roles beyond enzymatic activity. We delve into the basics of sGC expression regulation, from its transcriptional regulation to its interaction with proteins, placing particular emphasis on evidence thus far demonstrating the actions of each sGC subunit in different tumor models. Exploring the roles of sGC subunits in cancer offers a valuable opportunity to enhance our understanding of tumor biology and discover new therapeutic avenues.